La Iglesia de los llamados por Cristo pro-voca (Teología, 2020)
In this article, Monsignor Osvaldo Santagada introduces the topic of priestly ministryand the question about its meaning in changing times. From his experience of 49 yearsof ministry, the author presents his contributions towards a theological renewal ofpriestly life. The wealth of sources that the author evokes and his own experience leadthe reader through the topics of faith, prayer, love and the place of the Christian communityin the life of a priest.
Keywords: Sacred Order; Ministry; Holiness; Vocation; Love for Christ